Influenza Vaccine Effectiveness and Statin Use Among Adults in the United States, 2011–2017. (27th October 2018) - Havers, Fiona P; Chung, Jessie R; Belongia, Edward A; McLean, Huong Q; Gaglani, Manjusha; Murthy, Kempapura; Zimmerman, Richard K; Nowalk, Mary Patricia; Jackson, Michael L; Jackson, Lisa A; Monto, Arnold S; Petrie, Joshua G; et al.
Abstract: Background: Statin medications have immunomodulatory effects. Several recent studies suggest that statins may reduce influenza vaccine response and reduce influenza vaccine effectiveness (VE). Methods: We compared influenza VE in statin users and nonusers aged ≥45 years enrolled in the US Vaccine Effectiveness Network study over 6 influenza seasons (2011–2012 through 2016–2017). All enrollees presented to outpatients clinics with acute respiratory illness and were tested for influenza. Information on vaccination status, medical history, and statin use at the time of vaccination were collected by medical and pharmacy records. Using a test-negative design, we estimated VE as (1 – OR) × 100, in which OR is the odds ratio for testing positive for influenza virus among vaccinated vs unvaccinated participants. Results: Among 11692 eligible participants, 3359 (30%) were statin users and 2806 (24%) tested positive for influenza virus infection; 78% of statin users and 60% of nonusers had received influenza vaccine. After adjusting for potential confounders, influenza VE was 36% (95% confidence interval [CI], 22%–47%) among statin users and 39% (95% CI, 32%–45%) among nonusers. We observed no significant modification of VE by statin use. VE against influenza A(H1N1)pdm09, A(H3N2), and B viruses were similar among statin users and nonusers. Conclusions: In this large observational study, influenza VE against laboratory-confirmed influenza illness was not affected by current statin use among persons aged ≥45 years. Statin use did not modify the effect of vaccination on influenza when analyzed by type and subtype. Abstract : In a study of 11692 outpatients aged ≥45 years with acute respiratory illness, statin use had no significant effect on influenza vaccine effectiveness against laboratory-confirmed influenza. Statin use did not modify the effect of vaccination on influenza when analyzed by type/subtype.